PENERAPAN PROFESIONALISME DAN INDEPENDENSI AUDITOR TERHADAP TINGKAT MATERIALITAS (Program Studi Akuntansi | Fakultas Ekonomi dan Bisnis | Universitas Komputer Indonesia, 2022)
The purpose of this study is to determine how professionalism and independence’s auditor affect the level of materiality at 9 Public Accounting Firms in Bandung. This study used descriptive and verification methods using multiple linear regression analysis. The results of this study show that auditor’s professionalism has a strong effect on the materiality level, while independence has a moderate effect on the materiality level. The conclusion is the higher professionalism and independence of an auditor, the better materiality determining considerations. Keywords : Auditor’s Professionalism, Independence, and Materiality Level.